α/β-Peptides as Nanomolar Triggers of Lipid Raft-Mediated Endocytosis through GM1 Ganglioside Recognition - Anasztázia Hetényi; Enikő Szabó; Norbert Imre; Kaushik Nath Bhaumik; Attila Tököli; Tamás Füzesi; Réka Hollandi; Peter Horvath; Ágnes Czibula; Éva Monostori; Mária A. Deli; Tamás A. Martinek (MDPI AG, 2022)
Cell delivery of therapeutic macromolecules and nanoparticles is a critical drug development challenge. Translocation through lipid raft-mediated endocytic mechanisms is being sought, as it can avoid rapid lysosomal degradation. Here, we present a set of short α/β-peptide tags with high affinity to the lipid raft-associated ganglioside GM1. These sequences induce effective internalization of the attached immunoglobulin cargo. The structural requirements of the GM1-peptide interaction are presented, and the importance of the membrane components are shown. The results contribute to the development of a receptor-based cell delivery platform.